Organizational Member Involvement in Physical Activity Coalitions Across the United States: Development and Testing of a Novel Survey Instrument for Assessing Coalition Functioning. (June 2015) - Bornstein, Daniel B.; Pate, Russell R.; Beets, Michael W.; Saunders, Ruth P.; Blair, Steven N.
Introduction. Coalitions are often composed of member organizations. Member involvement is thought to be associated with coalition success. No instrument currently exists for evaluating organizational member involvement in physical activity coalitions. This study aimed to develop a survey instrument for evaluating organizational member involvement in physical activity coalitions. The study was carried out in three phases: (a) developing a draft survey, (b) assessing the content validity of the draft survey, and (c) assessing the underlying factor structure, reliability, and validity of the survey. Method. A cross-sectional design was employed. In Phase 1, a team of experts in survey development produced a draft survey. In Phase 2, the content validity of the draft survey was evaluated by a panel of individuals with expertise in physical activity coalitions. In Phase 3, the survey was administered to 120 individuals on local-, state-, and national-level physical activity coalitions. Responses were subjected to an exploratory factor analysis in order to determine the survey's underlying factor structure, reliability, and validity. Results. Phases 1 and 2yielded a survey instrument with demonstrated content validity. Phase 3 yielded a three-factor model with three subscales: Strategic Alignment, Organizational Alignment, and Providing Input. Each subscale demonstrated high internal consistency reliability and construct validity. Discussion. The survey instrument developed here demonstrated sound psychometric properties and provides new insight into organizational member involvement in physical activity coalitions. This instrument may be an important tool in developing a more complete picture of coalition functioning in physical activity coalitions specifically and health-based coalitions overall.